2005
DOI: 10.1002/jso.20358
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities of adenocarcinomas of the esophagus and esophagogastric junction

Abstract: During the last few decades there has been an alarming rise in the incidence of tumors originating at the esophagogastric junction (EGJ) [1]. The reason for this is unknown. Tumors of the EGJ can be categorized in two types of cancer divided according to their anatomical origin: distal esophageal adenocarcinoma and adenocarcinoma of the gastric cardia. However, due to their location, in the transitional zone of the esophagus and stomach, there is constant debate about the proper classification, staging, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 72 publications
(59 reference statements)
2
31
0
5
Order By: Relevance
“…[24][25][26] Consequently, these authors have advocated staging and treating these tumors as esophageal cancer. 25,27 Whether or not the patient population under study influenced our results is worth investigating, gastroesophageal junction cancer is common in China, and almost all tumors in this population are centered in the proximal stomach, in contrast to the vanishingly rare distal esophageal adenocarcinoma above the gastroesophageal junction. 2,11,[28][29][30] In a recent study from a high-volume medical center in China, Taiwan, the investigators did not find a single case of such cancer over a 20-year period.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Consequently, these authors have advocated staging and treating these tumors as esophageal cancer. 25,27 Whether or not the patient population under study influenced our results is worth investigating, gastroesophageal junction cancer is common in China, and almost all tumors in this population are centered in the proximal stomach, in contrast to the vanishingly rare distal esophageal adenocarcinoma above the gastroesophageal junction. 2,11,[28][29][30] In a recent study from a high-volume medical center in China, Taiwan, the investigators did not find a single case of such cancer over a 20-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Catenacci, 1 Gustavo Cervantes, 1 Soheil yala, 1 Erik a. nelson, 2 Essam El-Hashani, 1 Rajani Kanteti, 1 Mohamed El dinali, 1 Rifat Hasina, 1 Johannes Brägelmann, 1 Tanguy Seiwert, 1 Michele Sanicola, 3 Les Henderson, cooperative signaling may result in more aggressive phenotypes, (iii) and/or RON signaling may render resistance to MET inhibition (and vice versa). Here we show that RON is indeed highly expressed, and that MSP, RON, HGF and MET co-expression and co-activation is frequent and prognostic of survival in our GEC patient cohort.…”
Section: Ron (Mst1r) Is a Novel Prognostic Marker And Therapeutic Tarmentioning
confidence: 99%
“…Adenocarcinoma of the esophagogastric junction (EGJ) has shown an increasing trend over the last decades, particularly in Western countries [1,2]. In contrast, studies on the incidence of EGJ adenocarcinoma have found no evidence of changing trends in Korea [3,4].…”
Section: Introductionmentioning
confidence: 99%